Acute Deterioration of Pulmonary Arterial Hypertension (PAH) in a Patient with Neurofibromatosis Type 1 (NF1) - Seiya Tanaka; Fuko Kawahara; Taro Miyamoto; Satoshi Tsurusaki; Yoshihito Sanuki; Kiyoshi Ozumi; Takashi Harada; Hiromi Tasaki (Case Reports in Cardiology)
A 56-year-old woman was diagnosed as having chronic obstructive pulmonary disease with heavy smoking. Mild pulmonary hypertension (mean pulmonary arterial pressure: 31 mmHg) was detected at the first visit. She was diagnosed with pulmonary hypertension due to pulmonary disease and medicated only with bronchodilators. Simultaneous, multiple freckling in the trunk of her body and café au lait macules in her back with some cutaneous neurofibromas were also detected. A plastic surgeon removed one of the neurofibromas and pathologically diagnosed it as neurofibromatosis type 1 (NF1). We finally rediagnosed her with pulmonary hypertension with unclear and/or multifactorial factors when she deteriorated 1 year after being treated only with bronchodilators. We then administrated upfront combination therapy with macitentan and tadalafil. Mean pulmonary arterial pressure rapidly improved. Learning Objective. Pulmonary arterial hypertension (PAH) in neurofibromatosis type 1 (NF1) can occur due to lung disease or due to certain involvement of pulmonary arteries, or a combination of both. Increased awareness of PAH in NF1 is very important for patients survival. The current therapeutic strategy is almost identical to that of idiopathic PAH; however, there is no clinical evidence. Insights gained from clinical experiences should help identify promising novel therapeutic approaches in NF1-PAH.